ANALISIS PENGGUNAAN ABU CANGKANG TELUR SEBAGAI FILLER TERHADAP KUAT TEKAN BETON FC’ 30 MPa - Dwi Praja, Madhan Ismullah; Mulyani, Ely (Ensiklopedia of Journal, 2024)
This study aims to evaluate the effect of using eggshell ash as a substitute for filler in concrete with a compressive strength fc' 30 MPa. By replacing conventional filler with eggshell ash in varying proportions of 0.5%, 1%, 1.5% and 2%, this research tested the compressive and tensile strength of concrete. The research results show that the use of eggshell ash can increase the compressive strength of concrete, with the optimal proportion found at 1% substitution. The use of eggshell ash also has the potential to reduce waste and concrete production costs, thereby providing a more environmentally friendly and economical solution. Keywords: Concrete, Eggshell Ash, Filler, Compressive Strength